Sporadic Creutzfeldt-Jakob disease: a case report of long disease duration and difficulties in confirming the diagnosis with short literature review - Karolina Stanowska, Anna; Wach, Barbara; Herman-Sucharska, Izabela; Adamek, Dariusz (Folia Neuropathologica, 2021)
Creutzfeldt-Jakob disease (CJD) is a spongiform encephalopathy with the fatal outcome, caused by the accumulation of pathological prion protein in the central nervous system (CNS). CJD is classified into four types: sporadic (sCJD), familial or genetic (fCJD), iatrogenic (iCJD) and variant form (vCJD). The recognition of CJD is based on the clinical presentation, neuroimaging, electroencephalography and biochemical tests. The hyperintense signals in basal ganglia on brain magnetic resonance imaging (MRI), periodic sharp and slow wave complexes (PSWCs) in the electroencephalogram as well as presence of neuronal proteins such as protein 14-3-3 in the cerebrospinal fluid (CSF) support the diagnosis. The definite diagnosis of CJD still demands neuropathological confirmation. We report the case of a 56-year-old woman with the rapidly progressive cognitive impairment, motor dysfunctions and the fulminant neurological deterioration to akinetic mutism during the five weeks’ hospitalisation. The probable diagnosis of sCJD was based on medical history and characteristic findings in MRI. The positive result of the real-time quaking-induced conversion (RT-QuIC) test and presence of protein 14-3-3 were obtained post-mortem and definite diagnosis was confirmed by neuropathological examination. In this paper we would like to emphasize the difficulties in reaching the diagnosis and the need for a series of diagnostic examinations in different points of time to obtain the confirming results.